A prospective comparative study of ureterorenoscopy with and without DJ stenting for the management of ureteric stones - Prasad, Dinesh; Satani, Yogesh; Singh, Shivam; Gajera, Darpen (International Surgery Journal, 2021)
Background: Urolithiasis is the most common urological disease. Surgical treatment of ureteral stones consists of four minimally invasive modalities including ESWL, URS, PCNL, and laparoscopic or robotic-assisted stone surgery. URS and ESWL are the most widely used techniques. However, the use of ureteral stents for the treatment of ureteral stones is still controversial. Herein, we did a comparative study of URS with and without DJ stenting for the management of ureteric stones. Objectives of current study were to compare prevalence of post-operative complications in patients undergoing ureterorenoscopy without ureteral stenting as compared to patients undergoing stenting procedure, to study the frequency of morbidity in patients during post -operative period in both ‘stent’ and ‘no stent’ groups. Stone free-rate, operative time, complications, hospital stay and need for re-treatment in both groups will be determined. Methods: 50 patients with ureteric stones admitted in our hospital-SMIMER fulfilling our inclusion and exclusion criteria were randomly divided in two groups- patients in group A (25) underwent URS without DJ stenting and group B (25) underwent URS with DJ stenting. Results: URS without DJ stenting had less operative time, less postoperative complications like pain, requirement of analgesia, hematuria, UTI, dysuria, fever, less readmission rate and less hospital stay, similar stone free rate compared to URS with DJ stenting but it requires higher surgical endoscopy skills with urological expertise. Conclusions: Thus, after adequate training, URS without DJ stenting can be recommended as a safe alternative procedure than URS with DJ stenting for management of ureteric stones.